1, 3‐diarylpyrazolones as potential anticancer agents for non‐small cell lung cancer: Synthesis and antiproliferative activity evaluation. (1st March 2022) - Dahal, Achyut; Lo, Mary; Singh, Sitanshu; Vo, Huu; ElHage, Denzel; Jois, Seetharama D.; Murru, Siva
Abstract: A series of pyrazolone compounds with different substitution patterns have been synthesized using microwave‐assisted methods and evaluated their in vitro antiproliferative activity against human lung adenocarcinoma cell lines (A549 and NCI‐H522). Among the tested compounds, the pyrazolone P7 exhibited high antiproliferative activity against both A549 and NCIH522 cancer cell lines while being 10 times less cytotoxic to non‐cancerous cells. Moreover, our compounds P7 and P11 exhibited higher antiproliferative activity and selectivity against A549 and NCIH522 cells compared with the clinically approved drugs Afatinib and Gefitinib. The cell cycle analysis showed that the compound P7 and P11 arrests the cell cycle at G0/G1 phase, whereas the compounds P13 and P14 involved in G2/M phase arrest. The results from antiproliferative activity screening, cell cycle analysis, and kinase profiling indicate that the suitably substituted 1, 3‐diarylpyrazolones exhibit high antiproliferative activity against non‐small cell lung cancer cells. Abstract : 1, 3‐diarylpyrazolone compounds with halo‐aryl moieties showed promising antiproliferative activities against non‐small cell cancer cells, and the cell cycle analysis indicated that the di‐halocompounds arrest cell cycle at G2/M phase, whereas the mono‐halo pyrazolone compound arrests at G0/G1 phase.